2023
DOI: 10.1186/s40168-023-01468-3
|View full text |Cite
|
Sign up to set email alerts
|

Core-predominant gut fungus Kazachstania slooffiae promotes intestinal epithelial glycolysis via lysine desuccinylation in pigs

Abstract: Background Gut fungi are increasingly recognized as important contributors to host physiology, although most studies have focused on gut bacteria. Post-translational modifications (PTMs) of proteins play vital roles in cell metabolism. However, the contribution of gut fungi to host protein PTMs remains unclear. Mining gut fungi that mediate host protein PTMs and dissecting their mechanism are urgently needed. Results We studied the gut fungal commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 124 publications
2
13
0
Order By: Relevance
“…As piglets are already stressed during the weaning transition and administration takes time and handling, orally gavaging piglets daily is not practical. Additionally, the previous studies ( 18 , 42 ) both reported higher CFU in their dosages and more frequent administration than those used here. Here, if sample collection and treatment overlapped on the same day, samples were collected from pigs before treatment.…”
Section: Discussionmentioning
confidence: 37%
See 2 more Smart Citations
“…As piglets are already stressed during the weaning transition and administration takes time and handling, orally gavaging piglets daily is not practical. Additionally, the previous studies ( 18 , 42 ) both reported higher CFU in their dosages and more frequent administration than those used here. Here, if sample collection and treatment overlapped on the same day, samples were collected from pigs before treatment.…”
Section: Discussionmentioning
confidence: 37%
“…In this study, feeding K. slooffiae to piglets before and during the weaning transition was studied to determine impacts on health and growth performance. K. slooffiae has been consistently observed as a commensal in the pig gastrointestinal tract and has shown positive interactions with beneficial commensal bacteria in vitro ( 13–16 , 22 , 42 ); thus, we hypothesized that feeding K. slooffiae as a probiotic would improve piglet performance through: (a) indirect modulation of the combined microbiome ( 13 ); or (b) direct effects due to increased abundance of K. slooffiae in the gastrointestinal tract ( 18 , 19 ). Overall, we did not observe any improvements in piglet health or growth as an effect of K. slooffiae treatment, nor any detectable, sustained differences on alpha and beta diversity within either the bacteriome or mycobiome at day 49 as a direct result of supplementation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence shows that this sort of alternation of gut microbiota (often called dysbiosis) cause all sorts of health issues including diarrhea and inflammation ( Cerf-Bensussan and Gaboriau-Routhiau, 2010 ; Nagalingam et al, 2011 ; Arfken et al, 2020 ; Rutkowski et al, 2022 ; Uthaibutra et al, 2023 ). Overall, the balance of the intestinal microbiota is critical for maintaining the health of intestine and regulating the growth of the animal ( He et al, 2022 ; Hu et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…The gut microbiota is a complex microbial ecosystem that plays crucial roles in pig health, nutrient metabolism, and productivity (Chen et al, 2021a;Hu et al, 2023;Wang et al, 2022;Yang et al, 2022). Pig intestinal virus infections are prevalent in the global pig industry, but the large numbers of diverse viruses that inhabit the pig gut can greatly affect the structure and function of the gut microbial ecosystem (Shkoporov et al, 2022a).…”
Section: Introductionmentioning
confidence: 99%